Active Cluster Node Aggregation Scheme in Wireless Sensor Network Using Neural Network. (2016) - Eldhose, Elby K.; Jisha, G.
Abstract: Recent wireless communication technologies enable the deployment of large scale sensor network. Sensor node has limited power energy constraints act as the critical issue in the deployment. Hence, we must developed energy efficient methods to facilitate efficient data transmission between the nodes. In this paper we compare currently available energy efficient clustering methods. Also we propose a dynamic clustering node method using neural network. In Neural Network (NN) each node has to send data to all the nodes in the next layer, which in turns requires lots of energy. Instead of that we form a clusters, in each cluster elect cluster node. Cluster node processes the data and send directly to the base station or through other cluster node. We periodically change the cluster and cluster node in order to balance the energy constraints.